Case Report: Generalized motor tonic seizures characterized by paroxysmal fast activity on EEG in a Tonkinese cat - Brewińska, Laura; Drobot, Paulina; Wrzosek, Marcin (Frontiers in Veterinary Science, 2025)
Epilepsy is one of the most common neurological disorders in cats, affecting 1%−2% of the feline population. Feline epilepsy can often be managed with standard anti-seizure medications, which typically offer moderate to good seizure control. However, a small subset of cats may experience drug-resistant epilepsy and require alternative treatment options. The scientific understanding of the mechanisms underlying feline epilepsy has not yet reached the applicability seen in human studies. A deeper understanding of feline epilepsy will aid in developing effective treatment strategies. Electroencephalography (EEG) is an important tool for extending veterinary epilepsy classification. In the presented case, the disease was classified as idiopathic epilepsy with a Tier III confidence level according to the International Veterinary Epilepsy Task Force classification. The seizures were further characterized as primarily generalized tonic, with occasional focal seizures also observed, and the condition met the criteria for drug-resistant epilepsy. EEG findings revealed typical spike, sharp and slow wave, and polyspike activity, along with atypical paroxysmal fast activity. Non-standard treatment with phenytoin demonstrated potential efficacy in this case.